The positive relationship between ocean acidification and pollution. Issue 1 (15th February 2015) - Zeng, Xiangfeng; Chen, Xijuan; Zhuang, Jie
Graphical abstract: Ocean acidification, pollution, and their interactions. Highlights: Ocean acidification and pollution exert combined effects on marine ecosystems. Ocean acidification and pollution facilitate each other. Pollution-affected respiration acidifies ocean more than carbon dioxide uptake. Coastal regions are more vulnerable to the negative impact of ocean acidification. Abstract: Ocean acidification and pollution coexist to exert combined effects on the functions and services of marine ecosystems. Ocean acidification can increase the biotoxicity of heavy metals by altering their speciation and bioavailability. Marine pollutants, such as heavy metals and oils, could decrease the photosynthesis rate and increase the respiration rate of marine organisms as a result of biotoxicity and eutrophication, facilitating ocean acidification to varying degrees. Here we review the complex interactions between ocean acidification and pollution in the context of linkage of multiple stressors to marine ecosystems. The synthesized information shows that pollution-affected respiration acidifies coastal oceans more than the uptake of anthropogenic carbon dioxide. Coastal regions are more vulnerable to the negative impact of ocean acidification due to large influxes of pollutants from terrestrial ecosystems. Ocean acidification and pollution facilitate each other, and thus coastal environmental protection from pollution has a large potential for mitigating acidification risk.